Literasi IPAS: Model Pembelajaran LOK-R pada Siswa di Madrasah Ibtidaiyah - Khasanah, Ahadiyah Mauidhotul; Sholihah, Mar’atus (Mitra PGMI: Jurnal Kependidikan MI, 2024)
This study aims to describe the steps of applying the LOK-R learning model to improve the science literacy of grade IV and V students at Madrasah Ibtidaiyah Kedungrejo. The LOK-R learning model includes planning, implementation, and evaluation, and is used to improve science literacy at MI Al-Islamiyah Kedungrejo. This research used a descriptive qualitative method with a field research approach. Data were collected through observation, interviews and documentation. The results showed that the LOK-R learning model was effective in improving students' science literacy. In the planning stage, teachers and students prepare materials and develop learning objectives. At the implementation stage, literacy activities, orientation, collaboration, and reflection were carried out. At the evaluation stage, the improvement in science literacy competencies was significant, with 32 out of 35 students showing improvement. Before implementation, only 15 students had good IPAS literacy, but after implementation, the number increased to 32 students. The LOC-R learning model is proven to be effective for improving IPAS literacy in science learning.